Pavement Manager at Risk in Construction of Hot Mix Asphalt - Hesham Ali; Mohamadtaqi Baqersad (Advances in Civil Engineering)
Pavement management is part science, part management, and part experience. After several decades of promoting pavement management, many road owners are still reluctant to use it as they lack the knowledge, the experience, or the confidence. The problem is further complicated by the emergence of a large list of new products and techniques that are self-proclaimed to achieve miracles but fall short. The outcome of this arrangement is that thousands of miles of roads still cost more to maintain than if effective pavement preservation techniques were used. This paper attempts to resolve this dilemma by introducing the role of Pavement Manager at Risk (PMAR), allowing a Pavement Manager to offer a long-term pavement preservation service to a client in return for a fixed per-mile premium. This allows the knowledgeable Pavement Manager, who would typically be a Pavement Engineer or a practitioner with extensive knowledge and experience, to implement effective pavement preservation techniques and share the economic benefit with the owner. In this study, the responsibilities of the Pavement Manager at Risk (PMAR) will be introduced. The type of analysis it needs to run will be demonstrated in a case study. In this paper, a sample analysis is presented to present the financial aspects of managing a network of local roads. Pavement treatment cost, pavement condition, and treatment life extension in addition to the admin, mobilization, striping, and occasional patches expenses are presented. The benefits and risks of this approach are described.